2020
DOI: 10.1093/inthealth/ihz094
|View full text |Cite
|
Sign up to set email alerts
|

Success of malaria chemoprophylaxis for outbound civil and military travellers in prevention of reintroduction of malaria in Sri Lanka

Abstract: Background Sri Lanka was certified as malaria-free in September 2016. However, the continuous presence of the malaria vector poses serious risks of reintroduction of the disease. Chemoprophylaxis and advice on malaria preventive behaviour for international travellers is a key strategy adopted to reduce the risk of imported malaria. Methods We conducted an efficiency study of malaria chemoprophylaxis for civilian and military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Prevention of malaria in Sri Lankan travellers is yet another strategy being implemented by the AMC to reduce incidence, morbidity and mortality due to imported malaria. Studies have shown that malaria chemoprophylaxis is well tolerated by travellers with a protective efficacy of 100% amongst those who complied [ 14 ]. The AMC provides malaria chemoprophylaxis free-of-charge to any traveller destined for a malaria endemic country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention of malaria in Sri Lankan travellers is yet another strategy being implemented by the AMC to reduce incidence, morbidity and mortality due to imported malaria. Studies have shown that malaria chemoprophylaxis is well tolerated by travellers with a protective efficacy of 100% amongst those who complied [ 14 ]. The AMC provides malaria chemoprophylaxis free-of-charge to any traveller destined for a malaria endemic country.…”
Section: Discussionmentioning
confidence: 99%
“…The AMC provides malaria chemoprophylaxis free-of-charge to any traveller destined for a malaria endemic country. Yet, despite the wide availability of anti-malarial chemoprophylaxis at the AMC Headquarters and Offices of the Regional Malaria Officer travellers to malaria endemic countries rarely obtain these medicines, and even when they do, adherence to the prophylaxis regime has been poor [ 14 , 44 ]. Between 2015 and 2023, of the 30 patients who developed severe malaria, only five had obtained prophylaxis and they too had not taken it as advised (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that compliance in military troops was worse than civilians [ 32 ], as seen in studies of Marie-Aude Creach et al in which the prophylaxis compliance in troops was 56.6% [ 42 ]. In contrast, there was a different result seen in a Sri Lankan study with a compliance rate 90.3% in the civilian group and 100% in the military group [ 43 ]. In our study, the compliance rate (59.6%) is much lower than civilian compliance rates seen in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoprophylaxis is an effective tool to minimize the risk of malaria while resident in an endemic area, 2 and may be offered to non-immune travelers moving from a non-endemic area (for malaria transmission) to an endemic area, permanent residents of endemic areas where disease transmission is seasonal, or for special subgroups (children, pregnant women) in areas with year-round malaria transmission. 3 For non-immune travelers, chemoprophylaxis may be given as primary prophylaxis (a schizonticide agent given before, during, and after travel in an endemic area) or as terminal prophylaxis (hypnozoiticide agent against P. vivax given after leaving the endemic area).…”
Section: Introductionmentioning
confidence: 99%